Meaning and Void : Inner Experience and the Incentives in People?s Lives. - Klinger, Eric (University of Minnesota Press, 1973)
In a wide-ranging theory of the way people function, the author shows how their inner lives depend upon and in turn influence their commitments to goals or incentives.